The Edinburgh critical history of middle ages and Renaissance philosophy - LaZella, Andrew; Lee, Richard A., Jr (Edinburgh critical history of philosophy., 2020)
A team of leading international scholars examine Middle Ages and Renaissance philosophy from the perspective of themes and lines of thought that cut across authors, disciplines and national boundaries, opening up new ways to conceptualise the history of this period within philosophy, politics, religious studies and literature.